THE RELATIONSHIP OF GOOD UNIVERSITY GOVERNANCE AND STUDENT SATISFIED AT INSTITUT TEKNOLOGI BATAM - Dwipananda, Rizki Fadhel; Aswirawan, Maria Yosefina Meinadia Sekarkinanti; Jufri, Muhammad; Rahim, Rida; Nursyafitri, Amelia (Maqdis: Jurnal Kajian Ekonomi Islam, 2024)
The purpose of this study is to examine the influence of good university governance on the quality of teaching staff and student satisfaction. Research data was collected using a questionnaire and obtained 160 respondents who were active undergraduate level 1 students at the Batam Institute of Technology. This research is quantitative research and uses smartPLS in data processing. The results of this research found that good university governance has a significant effect on the quality of teaching staff and student satisfaction. This research provides insight that the implementation of good university governance will have a positive influence on the reputation and quality of higher education. These results can be used as a reference in higher education management to achieve the mission of a world-class university and implement the independent campus policy.